Matične knjige s preloma 19. in 20. stoletja kot zrcalo jezikovne politike med Muro in Savo - Lipavic Oštir, Alja (Slavia Centralis, 2024)
The analysis of the introduction of Slovene into the registers of the Lavantine diocese between 1870 and 1919 shows that German was replaced by Slovene in 92.4% of parishes as a decision of the same parish priest or that of his re placement. In 7.5% of parishes, German was preserved until 1918/1919 (in the form of a linguistic continuum in towns and parishes along the border or close to the border). Individual deaneries partly implemented a language policy regarding language change, however, the dichotomy of town vs. countryside did not decisive a decisive role. The decisive role was played by the individual parish priest and his national commitment, possibly countered only by his own highly developed multilingualism and language switching in everyday life. In this context, the present research allows also for identifying parallels with the introduction of Slovene into education.
Keywords: civil registers; German language; jezikovna politika; language policy; Lavantine diocese; Lavantinska škofija; matične knjige; multilingualism; ne zaključna dela; nemščina; Slovene language; slovenščina; večjezičnost